ANALISIS BIBLIOMETRIK DALAM STUDI BUDAYA ORGANISASI: SEBUAH PERKEMBANGAN LITERATUR - Zahra Zaharanura, Zahra; Siwi Agustina, Tri; Ekowati, Dian (Jurnal Pijar, 2024)
Culture plays a crucial role in maintaining the competitive advantage of an organization and determining the success or failure of achieving organizational goals. This research aims to fill the gap in previous studies on organizational culture by using more recent data, specifically summarizing discussions published during the 2019-2023 period. The research method used is a bibliometric literature review analysis, utilizing VOSviewer software to analyze the data. The data used comes from the Scopus database, using Publish or Perish from 2019-2023, with 158 articles selected as samples in the study. This study reviews the ten most cited articles. The results show that knowledge management, operational performance, culture, job satisfaction, innovation, commitment, employees, and green innovation are variables frequently studied in relation to organizational culture. The theme of organizational culture remains a research focus in recent years